Presidential Address: Tillers and Toilers: The Rise and Fall of Populism in Canada in the 1890s - Cook, Ramsay (Historical Papers / Communications historiques, 1984)
AbstractAs part of his on-going research upon religion and reform in late 19th century Canada, the author focuses on the efforts of the Patrons of Industry to ally with the labour movement. The author explores the attempts at cooperation between the two groups, and posits reasons for their failure to achieve a lasting and effective alliance. He examines the origins and policies of each group and outlines the grounds on which, participants believed, cooperation and alliance were both possible and desirable. The leader in this attempted farm-labour populist alliance was George W. Wrigley, from 1892 to 1896 the editor of the Canada Fanners' Sun, the Patron's weekly newspaper. He was the spokesman for a religiously based reformism which advocated the application of Chris- tian principles to everyday life. Wrigley saw an identity of interests between farmers and labourers, both of whom were producers who were victimized by the abuse of the system. Against these forces, organization and cooperation were necessary to ensure that the public interest would triumph over the private. Labour spokesmen and agrarian refor- mers shared the ideology cf agrarianism, "the conviction that man's most natural, healthy, even divinely inspired, activity was working on the land. " Both agreed that the farmer and the industrial worker each received insufficient return for their efforts, because the unproductive classes dominated the economy. Only an alliance committed to economic freedom, cooperation and democracy could eradicate the forces of privilege, unbridled competition and monopoly.While this alliance could point to some substantive achievements, ultimately it was a failure. The idea of cooperation received only modest support from the membership of both groups, while the leadership quickly became disillusioned by the slow pace of success. When the Patrons achieved a measure of political support in Ontario, they were unused to political power; they appeared indecisive and directionless as they debated tactics. Furthermore, the leadership often could not set aside their earlier attachments to either the Liberal or Conservative parties and wholeheartedly support the Patrons' political objectives. Hence internal divisions coupled with the return of prosperity late in the 1890s finally destroyed the country's first potentially successful protest party.